2014
DOI: 10.1007/s00421-014-2845-6
|View full text |Cite
|
Sign up to set email alerts
|

Atrial functional and geometrical remodeling in highly trained male athletes: for better or worse?

Abstract: A proportion of athletes with enlarged LA and RA showed different atrial contractile performance, likely resulting in atria working at higher wall stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 29 publications
3
53
0
2
Order By: Relevance
“…In our study, the functional assessment of LA was feasible in nearly all examined athletes. The important information is that LA STE derived strain was independent of LA size, which had been postulated before based on smaller sample groups (N < 25) (D'Ascenzi et al, 2012; Gabrielli et al, 2014). LA systolic and diastolic strains in young athletes are also independent of the parameters of left ventricular hypertrophy and left ventricle filling pressure.…”
Section: Discussionmentioning
confidence: 61%
“…In our study, the functional assessment of LA was feasible in nearly all examined athletes. The important information is that LA STE derived strain was independent of LA size, which had been postulated before based on smaller sample groups (N < 25) (D'Ascenzi et al, 2012; Gabrielli et al, 2014). LA systolic and diastolic strains in young athletes are also independent of the parameters of left ventricular hypertrophy and left ventricle filling pressure.…”
Section: Discussionmentioning
confidence: 61%
“…Four studies published by D'Ascenzi et al and two studies by Gabrielli et al had different aims and, more importantly, population samples.…”
Section: Resultsmentioning
confidence: 99%
“…While both disease and training may produce atrial enlargement, strain may aid in differentiating between pathological and physiological remodeling; in atrial fibrillation (Kuppahally et al 2010) and other pathologies associated with atrial enlargement, peak atrial strain is depressed (Mondillo et al 2011). A recent study found that while a majority of endurance athletes had LA strains similar to controls, a subgroup was characterized by impaired strain, and suggested that this subgroup may operate at higher LA wall stress (Gabrielli et al 2014). Conversely, our data and others have demonstrated enhanced or preserved atrial strain following both short-and long-term endurance training (Gabrielli et al 2012), while LA strain is depressed in patients with hypertrophic cardiomyopathy (Gabrielli et al 2012).…”
Section: Myocardial Deformation Mechanicsmentioning
confidence: 96%